THE IMPORTANCE OF CHILD PROTECTION IN THE SWIMMING POOL - Bernáth, Gréta Andrea; Bíró, Melinda (Stadium - Hungarian Journal of Sport Sciences, 2024)
Most of the coaches have a positive, supportive attitude towards athletes. Physical and emotional abuse of children is no longer part of the pedagogical practice of coaches these days, but unfortunately, this is not always the case. We examined two sports, swimming and water polo. We were interested in what form of abuse appears among athletes. How abused athletes share their experiences and process what happened. We used a questionnaire method in the study. One hundred seventeen people participated in the research: 63 women (53.8%) and 54 men (46.2%). The results demonstrated that all types of abuse (physical, mental, physical, and sexual) occurred in the examined sample. The majority of those interviewed reported various "punishments" such as some exercise, push-ups (73.5%), or additional swimming (69.2%). Many of them (28.8%) were shamed and humiliated. 43.2% of the respondents do not consider physical or mental abuse to be acceptable, but there are some things where they are more lenient. Nearly 17 percent assume intense pressure on the head is acceptable, and 30% of athletes partially or fully agree that "the coach has the right to use physical punishment to educate and discipline the child. Respondents shared their experiences mostly with their mother (41.9%), father (26.5%), or friends (26.5%). More than half of the respondents (59.8%) tried to suppress their grievances, and many (58.1%) also believed these experiences would accompany them throughout their lives.